Computational approach towards understanding structural and functional role of cytokinin oxidase/dehydrogenase 2 (CKX2) in enhancing grain yield in rice plant. Issue 4 (3rd March 2020) - Gouda, Gayatri; Gupta, Manoj Kumar; Donde, Ravindra; Kumar, Jitendra; Vadde, Ramakrishna; Mohapatra, Trilochan; Behera, Lambodar
Abstract: Cytokinin oxidase/dehydrogenase (CKX) is the only known enzyme associated with irreversible degradation of cytokinins in plants. CKX2 contains flavin adenine dinucleotide (FAD) domain. Earlier studies utilising antisense & hpRNAi suppression techniques in mutant/transgenic rice plants revealed that when CKX2 binds with FAD, CKX2 expression reduces, which in turn causes cytokinin aggregation in inflorescence meristem that subsequently enhances both branches and grain number resulting in increased grain yield. Owing to the non-existence of complete three-dimensional structure of CKX2, insight into the structure and function of CKX2 and its relationship with its cofactor FAD is still a topic of debate. In the present study, computational approach was employed to estimate the three-dimensional structure of CKX2 through comparative modelling approach. Later, CKX2 and FAD interaction study was performed to understand the underlying mechanism involved with reduced expression of CKX2. Molecular dynamic simulation studies of both CKX2 and CKX-FAD complex revealed that after binding with FAD, CKX2 experienced increased pressure and reduced RMSD, potential energy and free energy landscape energy, which in turn lessen anti-correlation between almost all α and β strands and random motion of C-α, subsequently reducing CKX2 expression. In near future, these information can be utilised for increasing rice yield under irrigated field condition by introgression of Gn1a gene through marker assisted back-crossing breeding. Abbreviations: GROMACS GROningen MAchine for Chemical Simulations NPT Constant Number of Particles, Volume and Temperature RMSD Root Mean Square Deviation RMSF Root Mean Square Fluctuations QTL quantitative trait loci FAD flavin adenine dinucleotide NVT Constant Number of Particles, Pressure and Temperature LINCS Linear Constraint Solver CKX2 Cytokinin oxidase/dehydrogenase 2 MM/PBSA Molecular Mechanics/Poisson–Boltzmann surface area SDF Structure Data File Communicated by Ramaswamy H. Sarma